10 Navy men liable for Viets' death - Cardinoza, Gabriel L. (Philippine Daily Inquirer, 2017)
Five of the Vietnamese fishermen apprehended off Bolinao town during their interrogation by the Philippine Coast Guard. They have since been detained in their fishing boat